The Adipocyte and Adaptive Immunity - Song, Jianfeng; Deng, Tuo (Frontiers in Immunology, 2020)
Not only do Adipocytes have energy storage and endocrine functions, but they also play an immunological role. Adipocytes are involved in adaptive immunity to mediate the pathological processes of a variety of chronic inflammatory diseases and autoimmune syndromes. The adaptive immune response consists of T cell-mediated cellular immunity and B cell-mediated humoral immunity. Obese adipocytes overexpress MHC class II molecules and costimulators to act as antigen-presenting cells (APCs) and promote the activation of CD4+ T cells. In addition, various adipokines secreted by adipocytes regulate the proliferation and differentiation of T cells. Adipokines are also involved in B cell generation, development, activation, and antibody production. Therefore, adipocytes play an important role in B cell-mediated adaptive immunity. This review describes how adipocytes participate in adaptive immunity from the perspective of T cells and B cells, and discusses their role in the pathogenesis of various diseases.